The Role of the Policy Process on Health Service Reconfigurations: Evidence, Path Dependency and Framing; Comment on “‘Attending to History’ in Major System Change in Healthcare in England: Specialist Cancer Surgery Service Reconfiguration” - Juan I. Baeza (International Journal of Health Policy and Management, 2023)
Historically healthcare services have largely developed on an incremental basis, with various piecemeal changes and some notable policy leaps that illustrate a punctuated equilibrium health policy process. More recently policy-makers have attempted, successfully and unsuccessfully, to reconfigure healthcare services to address perceived problems in the delivery of important services such as stroke, cancer, and trauma. Perry et al provide a welcome addition to research in this area by focusing on the importance of history in a reconfiguration of cancer services in Greater Manchester (GM). Perry et al analyse how and why this configuration was successful after several failed attempts in the past and in this commentary, I want to reflect on the explanatory role health policy analysis can contribute to studying the reconfiguration of healthcare services.